(untitled) (Research, Society and Development, 2022)
It is known that population growth has caused a substantial increase in the production and consumption of goods, generating a large amount of solid waste. The city of Grajaú is located 580 KM from the capital São Luís, but it has no safe management and no effective flow for urban solids, there are many impacts on public health and the environment. In view of the environmental problems that have occurred in various ways, we will go after the problems caused by inactive dumps, in the city of Grajaú there are no sanitary landfills that would be correct. The present study had the function of analyzing the soil of the inactive dump by means of chemical indicators. For the present work, a bibliographic research was carried out to seek references between concepts, causes, solutions, characteristics and ideas. The research will develop from information through site observation and soil analysis. Where we will use the help of a digger to remove the three depth samples from the sites and I will use ALFAKIT to analyze the samples collected. The highest concentrations were Al3+ in samples P1 30 cm, P2 surface, P4 surface and P4 50 cm, Calcium + magnesium in samples P2 surface, and P2 10 cm. Nitrite was found in samples P1 surface, P1 30 cm, P2 surface, P2 10 cm, P3, P4 surface and P4 50 cm. Ammonia in samples P2 10 cm and P4 surface. The malefic indices prevent the appearance of plants, high values ​​of calcium + magnesium make it difficult for plants to absorb nutrients to develop.